The Effect of Assets Structure, Capital Structure, and Sales Growth on Company Value in 10 Companies on the Indonesia Stock Exchange Moderated by Profitability (Study on the Digital Sector) - Rio Johan Putra; Shiva Dewanti Nabila (Budapest International Research and Critics University, 2022)
Increasing digital business competition that is rapidly making companies have to adapt so that they can be noticed by investors. Until now, investors are getting smarter in making investment decisions, because this affects their investments for the long term. In this study, the author will conduct a test related to the effect of Asset Structure, Capital Structure, and Sales Growth on Firm Value at 10 Companies On the Indonesian Stock Exchange Moderated By Profitability. In this study, the author uses descriptive analysis, namely collecting, compiling, processing, and analyzing data in order to provide a situation so that conclusions can be drawn. The type of data used is quantitative data. The results showed that (1) asset structure had no significant effect on firm value; (2) capital structure has no significant effect on firm value; (3) sales growth has no significant effect on firm value; (4) profitability is not able to moderate the influence of asset structure on firm value; (5) profitability is able to moderate the effect of capital structure on firm value; and (6) profitability is not able to moderate sales growth to firm value.